Performance of a New HPV Cervi-Collect Collection and Transportation Kit. (14th November 2011) - Chernesky, M.; Huang, S.; Jang, D.; Erickson, B.; Salituro, J.; Engel, H.; Gilchrist, J.; Neuscheler, P.; Mak, W. B.; Abravaya, K.
Abstract : Background . Liquid-based Pap (L-Pap) media are used for Pap and human papillomavirus (HPV) testing. Objectives . To compare RealTi m e High Risk (HR) HPV testing of a new collection kit (Cervi-Collect) and PreservCyt L-Pap specimens. To determine ease of use and safety of Cervi-Collect. Methods . L-Pap samples (n = 203 ) were tested with HC2 and RealTi m e HR HPV and Cervi-Collect with RealTi m e HR HPV. Discordant samples were genotyped. Results . L-Pap and Cervi-Collect specimens tested by RealTi m e HR HPV showed 93.1% agreement (Kappa 0.86). RealTi m e HR HPV and HC2 on L-Pap had 90.3% agreement (Kappa 0.80). RealTi m e HR HPV on Cervi-Collect and HC2 on L-Pap showed 88.2% agreement (Kappa 0.76). Sixteen of 21 samples which were HC2 negative and RealTi m e HR HPV positive on L-Pap or Cervi-Collect contained HR HPV genotypes. Eleven healthcare collectors were in strong agreement on a usability and safety questionnaire. Conclusion . Cervi-Collect samples were easy to collect and showed strong agreement with L-Pap samples tested with RealTi m e HR HPV or HC2.